How to Study for Students with Visual Specialties (X) with Achievements in the Field of Musabaqah Tilawatil Qur'an (MTQ) - Asri Reski Ilmiawan; Damri Damri (Universitas Muhammadiyah Enrekang, 2022)
This study discusses how to learn for blind students with special needs (X) who excel in the field of Musabaqah Tilawatil Qur'an (MTQ). This research is motivated because the author found a blind student who excels in the field of Musabaqah Tilawatil Qur'an (MTQ) even though he has visual impairment. The purpose of this study was to determine the method of learning the Qur'an for blind students (X), how blind students X in learning to read the Qur'an, the time of learning the Qur'an for visually impaired students (X), the media used by blind students. (X) in learning the Qur'an and what achievements have been achieved by blind students (X) in the field of MTQ. This study uses qualitative research methods with the type of case study research. The subject in this study was a visually impaired student of class X 2021 from the Department of Extraordinary Education, Faculty of Education, UNP who was totally blind. Data collection techniques used are interviews, observation and documentation. The results of this study found that X used the practice method in learning to read the Qur'an, X began listening to the Qur'an from MP3 since he was a baby and began learning to memorize the Qur'an at the age of 3 years. many years. In addition to studying with the Koran teacher, X also studies orthodox at home to repeat lessons, X studies with the Koran teacher once a week for 2 hours. X has achieved many achievements in the field of MTQ.